Adenosine Inhibits Tissue Factor Expression by LPS-stimulated Human Monocytes: Involvement of the A3 Adenosine Receptor - Broussas, Matthieu; Cornillet-Lefèbvre, Pascale; Potron, Gérard; Nguyên, Philippe (Thrombosis and Haemostasis, 2002)
Tissue Factor (TF), an integral membrane glycoprotein that initiates the extrinsic pathway of blood coagulation, is thought to play a major part in coronary acute events. Adenosine, an endogenous nucleoside produced by the degradation of intracellular adenosine triphosphate, has been shown to exert many cardioprotective effects via an inhibition of platelets and neutrophils. This study was conducted to determine whether adenosine (ADO) could modulate the expression of TF by human monocytes. We found that ADO inhibited TF antigen and activity on endotoxin-stimulated monocytes in a dose-dependent manner. The mechanism was at least pre-translational since ADO caused a change in the TF mRNA level. Using ADO receptor-specific analogs, we showed that highly selective A3 agonist N6-(3-iodobenzyl)-adenosine-5’-N’-methyluronamide (IB-MECA) inhibited LPSinduced TF activity expression more potently than A1 agonist R-phenylisopropyladenosine (R-PIA) and A2 agonist CGS 2180. Furthermore, A1/A3 antagonist, xanthine amine congener (XAC) blocked the effect of ADO whereas A2a, A2b and A1 antagonists were ineffective. In addition, we observed that ADO agonists inhibited monocyte TF expression in LPS-stimulated whole blood. The rank order of agonist potency suggested that A2 and A3 receptors might be involved (2-Cado > CGS = IB-MECA > R-PIA). This was supported by the fact that A2 and A3 antagonists reversed the action of 2-Cado. We conclude that TF inhibition by ADO on human purified monocytes involved A3 receptors.
Keywords: Tissue factor; adenosine; adenosine receptor; human monocytes